Measurements of ozone in the Antarctic atmosphere during August and September 1987 - Starr, Walter L.; Vedder, James F. (1989)
Mixing ratios changed dramatically for ozone in the austral polar stratosphere during August and September 1987. Data were obtained with an ultraviolet photometer mounted in the equipment bay of an ER-2 aircraft. Measurements were made between the latitudes of 53 and 72 deg S at pressure altitudes (U.S. Standard Atmosphere, 1976) up to 21 km in a series of flights from Punta Arenas, Chile, over the Palmer Peninsula. Additional data were obtained between 37 N and 53 deg S on the ferry flights leaving from and returning to Moffett Field, California. The sampling-collecting system and the analytical techniques are described. In September the mixing ratios for ozone at pressure altitudes above 15 km in the southernmost part of the flights over the Palmer Peninsula were significantly lower than values for midlatitudes. The various latitudes of the ER-2 aircraft's encounters with the boundary of the region of depleted ozone lie between 59 and 71 deg S. Near the 425 K potential temperature surface and well within the vortex, the measured mixing ratio of ozone declined from about 2 parts per million by volume (ppmv) to about 0.6 ppmv during the period of the ER-2 flights. The distributions of ozone as a function of altitude indicate the presence of layering of ozone.